Greenhouse climate management and control systems - Cunha, J. B. (2013)
The technologies used in greenhouse production systems have developed considerably during the last decade. These improvements have taken place in several areas, such as the development of new building techniques and actuating equipments, modelling of the plant physiological processes and of the greenhouse climate, among many others. Nowadays, due to economic and environmental requirements, there is still a demand to improve the greenhouse climate management and control systems in order to optimise the production process. This paper addresses some of the software tools that are being implemented and tested with this purpose.